ANALYSIS BSI KC JOMBANG CUSTOMER INTEREST IN USING BSI MOBILE THROUGH THE FRAMEWORK TAM - Nur Holifah, Febylia; Elfira Maya Adiba (I-Finance Journal, 2024)
The purpose of this study was to analyze the effect of perceived ease of use, perceived usefulness, and user attitudes on customer interest in using BSI Mobile. The population of this study consisted of 968 BSI Mobile user customers registered at BSI KC Jombang in 2023, and the sample used was 284 customers selected using purposive sampling method with the criteria that respondents were at least 17 years old and had become BSI Mobile users. The research method used is quantitative with analysis techniques using the Structural Equation Model (SEM)-Partial Least Square (PLS). Data is collected through a google form questionnaire containing questions related to variables. The results of this study indicate that perceived convenience has a significant effect on perceived benefits, perceived convenience has a significant effect on user attitudes, perceived benefits have a significant effect on user attitudes, and user attitudes have a significant effect on customer interest in using BSI Mobile. The conclusion that efforts to improve perceived ease, perceived benefits, and user attitudes towards the BSI Mobile application will have a positive impact on customer interest in adopting and using BSI Mobile on an ongoing basis.